Resistensi Atas Kebijakan Pengelolaan Hutan (Studi Pada Masyarakat Orang Rimba di Provinsi Jambi) - Yusuf, Muhammad; Qodir, Zuly (Universitas Muhammadiyah Yogyakarta, 2014)
The purpose of this research to answer the reason why the Indigenous resistance are still continue against the TNDBâspolicy and TNDBâs r esponse as government representative to the Indigenous. With study case and ethnographyapproaches, this kind ofÂ research is a descriptive-qualitative research. The primer data are used through interviewand observation; the secondary data are also used from primary documents and secondary documents. The circum-stance ofÂ indigenous resistance is change from covered to open conflict because many intervention from the TNDBoffice. The effort resistance ofÂ closed form which are opening land continuously, selling natural resources, terrainselling, chattering to everyone, also absent from TNDBâs department call. Even the effort resistance of open formblocking the TNDBâs officer to enter the place, open debating and discussing individual and collective and collectiveforce behavior. The finding ofÂ this research shows the reason why the indigenous resistances are still continuing: 1).There is a disappointment in TNDBâs policy because it commits unilaterally from government, 2). The ruining ofindigenous law cause the function ofÂ law itself doesnât work anymore, 3). Cooperation and influence from outsider 4).Competitive natural resources management between indigenous with indigenous people, also indigenous with outsider5). The increase ofÂ living cost make indigenous forces to take risks either in closed form or open form.